The Roles of Anticipated Guilt, Neutralisation and Advertising Appeals in Consumers' Ethical Decision-Making - YANG, SHU-TING (2008)
In this study, first, the discrepancy between consumers'ethical belief and ethical intention was reported in the ethical context of whether to use plastic carrier bags in supermarkets. Second, the anticipated guilt and consumers'acceptance of neutralization techniques were found to play the important roles in ethical consumers'decision making process. A framework, based on the theory of planned behavior, incorporated anticipated guilt as a mediator between consumers' neutralization and ethical intention and this framework also included neutralization as a moderator between consumers' ethical belief and ethical intention. In addition, an experiment was established to illustrate whether different advertising appeals may have different effects on consumers'anticipated guilt and their ethical intention. Results showed that both appeals could exert positive influence on consumers' anticipated guilt as well as ethical intention. However, though guilt appeal could increase more anticipated guilt than informational appeal, their impact on consumers' ethical intention was not found significantly different. That was, both appeals could be applied to enhance consumers'ethical intention. Together the proposed theoretical framework with testing on effects of advertising appeals, this research might have important theoretical and managerial contributions.